Gut Feelings Questionnaire in daily practice: a feasibility study using a mixed-methods approach in three European countries. Issue 11 (8th November 2018) - Barais, Marie; van de Wiel, Margje W J; Groell, Nicolas; Dany, Antoine; Montier, Tristan; Van Royen, Paul; Stolper, Erik C F
Abstract : Objectives: The validated Gut Feelings Questionnaire (GFQ) is a 10-item questionnaire based on the definitions of the sense of alarm and the sense of reassurance. The purpose of the GFQ is to determine the presence or absence of gut feelings in the diagnostic reasoning of general practitioners (GPs). The aim was to test the GFQ on GPs, in real practice settings, to check whether any changes were needed to improve feasibility, and to calculate the prevalence of the GPs' sense of alarm and sense of reassurance in three different countries. Setting: Primary care, six participating centres in Belgium, France and the Netherlands. Participants: We performed a think-aloud study with 24 experienced Dutch GPs, GP trainees and medical clerks who filled in the GFQ after diagnosing each of six case vignettes. We then performed a feasibility study in two phases, using a mixed-method approach, with 42 French and Dutch GPs in the first phase and then 10 Belgian, 10 Dutch and 10 French GPs in the second phase. All GPs filled in the GFQ after each of eight consultations with patients presenting new complaints and were subsequently interviewed about the use of the GFQ. Outcome measures: GPs' experiences on using the GFQ in real practice, more specifically the average time needed for filling in the questionnaire. The prevalence of GPs' sense of alarm and sense of reassurance. Results: The modified version of the GFQ, created without altering the sense of the validated items, was easy to use in daily practice. The prevalence of the GPs' sense of alarm occurred during 23%–31% of the included consultations. Conclusions: After a two-step study and several minor adaptations, the final version of the GFQ proved to be a feasible and practical tool to be used for prospective observational studies in daily practice.